Guanxi as impetus? Career exploration in China and the United States - Jiwen Song, Lynda; Werbel, James D. (Career development international, 2007)
Purpose - The present paper seeks to analyze the role of social networks in the process of career exploration, including its main effect on search intensity, and moderation effect on the linkage between search intensity and job search confidence.Design methodology approach - It is a longitudinal design with 239 USA and 165 Chinese graduating students.Findings - Social networks in job search have greater effects on job search intensity in the USA sample. Moderation effects could be detected in the Chinese sample, and guanxi search (a Chinese reference to social networks) minimizes job search confidence and job satisfaction.Research limitations implications - Social networks, particularly guanxi search in China, could reflect interdependency in job search process, and might constrain job choice.Originality value - The paper examined the cultural differences of guanxi search construct, and compared the role of social networks (guanxi search) in cross-cultural settings.